KEWIRAUSAHAAN-SOSIAL BERBASIS ORGANISASI MASYARAKAT (ORMAS) (Studi Analisis mengenai Pemberdayaan Ekonomi Ummat atas Unit Usaha-Sosial Persis, NU, dan Muhammadiyah di Kabupaten Garut) - Deden Suparman (JURNAL ISTEK, 2012)
Globalization has accelerated development grow twisted science, technology, and business. However, the acceleration of development is not accompanied by equity. Community with one another, or one person with another person has entered the dilemma of social inequality that was incredible. This is caused by business practices that are not responsible, development projects that are not effective, and poor government policies, making development efforts more difficult inclusive, and the increasingly adverse impact on the environment, social injustice and bring economic social conflicts and political. Management rules of social organization is no different from the management of business organizations, except the vision and mission, which is characterized by social interests. A management expert, Peter Drucker in his book Innovation and Entrepreneurship (1985), based on his observations in America, concluded that there has been an inevitable shift from conventional economic management to the management of social economy. For example, in terms of employment. Examples of cases in job creation in business organizations, and even reduce its workforce, while the social organization of small and medium scale became a provider of new jobs. Attention and efforts to develop self-employment and entrepreneurship increased. By considering these trends, more is needed in systemic efforts to answer this question. Collaborative actions that are sustainable over the government, the business sector, NGOs, CBOs, academic world, as well as the audience are widely needed to create a development more inclusive and equitable. Union of Islam (Persis), Nahdhatul Ulama (NU) and Muhammadiyah is one of the Islamic community organizations as well as a religious organization, serves also as a social organization. Its existence can be challenged to promote good social role in the economic, social, and cultural. In the economic field, the three CBOs are required to be able to play real people inspire economic progress.In the context of the Garutan, concrete steps are required three CBOs play a major role to be a problem solver ke-ummatan economy. Because the majority of people belonging to disadvantaged areas Garut is a majority of the